Perspectives of innovation in logistic activities of enterprises - Bohdanov, Serhii (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The purpose of the article is to identify the advantages and conceptual perspectives of introducing innovations in the logistics activities of enterprises. Design/methodology/approach. The basic principles of the research are systematic and comparative methods, institutional and structural-functional approaches have been used. Findings. The article considers the peculiarities of application and development of innovations in logistic enterprises in modern conditions. The influence of innovations on the efficiency of logistics enterprises’ functioning is investigated. Innovations play a main role in providing quality services by enterprises. Finding and implementing the latest innovations will enable sustainable development of the enterprise and consolidate its position in a competitive market. The necessity of application of innovations in the activity of logistic enterprises is proved. The essence of the concept of "innovation" is formulated. The necessity of innovative development of enterprises, in particular logistics, is determined. The advantages of innovative development of logistics of the enterprise are indicated. Research limitations/implications. It has been proved the need for logistics capacity to detect hidden reserves in the enterprise and increase the return on a reasonable use of modern economic tools, improving the efficiency of logistics processes. Originality/value. Further research on the development of innovation system is actualized in the process of Ukraine’s integration into the world economy.